Elemental geochemistry of sediment core MD03-2685 - Nathan Stevenard; Catherine Kissel; Aline Govin; Camille Wandres (PANGAEA, 2024)
All elemental data were obtained with a X-Ray Fluorescence (XRF) core-scanner Avaatech 4th generation at the Laboratoire des Sciences du Climat et de l extquotesingleEnvironnement (LSCE), and calibrated using the Weltje et al., (2015) Multivariate Log-ratio Calibration (MLC).
In: Stevenard, N et al. (2024): Age model, elemental geochemistry and magnetic data of cores MD03-2673, MD03-2679 and MD03-2685 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.971917